A Spontaneous Complementary Mutation Restores the RNA Silencing Suppression Activity of HC-Pro and the Virulence of Sugarcane Mosaic Virus - Xu, Xiao-Jie; Li, Huan-Gai; Cheng, De-Jie; Liu, Ling-Zhi; Geng, Chao; Tian, Yan-Ping; Li, Xiang-Dong (Frontiers in Plant Science, 2020)
Cross-protection is a promising measure to control plant viral diseases. Reverse genetics had been recently adopted to generate attenuated mutants that have potential in cross-protection. But studies on the variability of the progeny viruses of the attenuated mutants are scarce. Sugarcane mosaic virus (SCMV; genus Potyvirus, family Potyviridae) is the prevalent virus inducing maize dwarf mosaic disease in China. Here, we showed that the substitution of arginine with isoleucine in the FRNK motif at position 184 of helper component-proteinase (HC-Pro) abolished its RNA silencing suppression (RSS) activity, drastically reduced the virulence and accumulation level of SCMV, and impaired the synergism between SCMV and maize chlorotic mottle virus. The attenuated mutant could protect maize plants from a severe infection of SCMV. However, a spontaneous mutation of glycine at position 440 to arginine in HC-Pro rescued the virulence and synergism with maize chlorotic mottle virus of SCMV and the RSS activity of HC-Pro. Similar results were obtained with tobacco vein banding mosaic virus and watermelon mosaic virus. These results provide novel evidence for the complementary mutation of potyviruses in maintaining the HC-Pro RSS activity and potyviral virulence and remind us of evaluating the potential risk of attenuated mutants thoroughly before applying for the control of plant viral diseases via cross-protection.